2014
DOI: 10.4238/2014.december.4.24
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic parameters of carcass and organ traits of broiler chickens

Abstract: ABSTRACT. The objective of this study was to estimate the genetic and environmental parameters for carcass, carcass part, and organ weights in a paternal strain of broiler chickens that was selected mainly for body weight at 42 days of age (BW42) to provide support for poultry genetic improvement programs. A total of 1448 chickens were used that resulted from the expansion of a pure paternal strain named TT, which was developed by Embrapa Suínos e Aves. The following weights were evaluated: BW42, chilled carca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
20
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 17 publications
7
20
2
Order By: Relevance
“…We found highly positive genetic (0.74) and phenotypic correlations (0.63) between BW42 and BMW. Venturini et al [18] also found genetic and phenotypic correlation coefficients of 0.86 and 0.84 between BW42 and BMW, respectively, which were consistent with our results. However, compared with Venturini et al’s result (0.7), we found a smaller genetic correlation between BW42 and LMW (0.3), likely due to the use of a different species.…”
Section: Discussionsupporting
confidence: 93%
“…We found highly positive genetic (0.74) and phenotypic correlations (0.63) between BW42 and BMW. Venturini et al [18] also found genetic and phenotypic correlation coefficients of 0.86 and 0.84 between BW42 and BMW, respectively, which were consistent with our results. However, compared with Venturini et al’s result (0.7), we found a smaller genetic correlation between BW42 and LMW (0.3), likely due to the use of a different species.…”
Section: Discussionsupporting
confidence: 93%
“…The heritability estimate for LW obtained from our population was 0.17. This was lower than the estimate of Venturini et al (2014), who reported a heritability of 0.33 for LW in broiler chickens. The heritability estimate for LP in this study was 0.18; this value is similar to that obtained by Wang et al (2011), who reported a heritability of 0.21 for LP in 20-week-old Rugao yellow chicken.…”
Section: Discussioncontrasting
confidence: 45%
“…Significant effect of hatch on BWT2, 4, 6 and 8 weeks was reported by Adeyinka et al (2006). Gaya et al (2006) and Venturini et al (2014) reported significant effect of hatch and gender on body weight variables in their study. Effect of generation on body weight variables has been found to be significant in a study where data on four generation were analysed (Larivière et al 2009).…”
Section: Average Daily Gainmentioning
confidence: 70%
“…20, 210.46, 744.33, 1351.30 and 2428.10 grams, respectively in Naked Neck broiler chickens. Venturini et al (2014) reported BWT42 to be 2224.39 grams in broiler chicken parent line which was evaluated for body weight, feed conversion and carcass traits. The mean values for body weight at 6, 20 and 40 weeks of age were 1190.2±4.1 g, 2125.9±3.7 g and 3086.26±3.8 g, respectively (Mishra et al 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation